2004
DOI: 10.1038/sj.onc.1207983
|View full text |Cite
|
Sign up to set email alerts
|

Induction of PDCD4 tumor suppressor gene expression by RAR agonists, antiestrogen and HER-2/neu antagonist in breast cancer cells. Evidence for a role in apoptosis

Abstract: The growth of human breast tumor cells is regulated through signaling involving cell surface growth factor receptors and nuclear receptors of the steroid/thyroid/retinoid receptor gene family. Retinoic acid receptors (RARs), members of the steroid/thyroid hormone receptor gene family, are ligand-dependent transcription factors, which have in vitro and in vivo growth inhibitory activity against breast cancer cells. RAR-agonists inhibit the proliferation of many human breast cancer cell lines, particularly those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
1
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(122 citation statements)
references
References 50 publications
3
114
1
4
Order By: Relevance
“…We have observed that PDCD4 expression was upregulated in Hep3B but rarely in HepG2 cells by TGF-b1 treatment (unpublished data). Recently, Afonia et al (2004) have reported that PDCD4 overexpression induced apoptosis PDCD4 in TGF-b1-induced apoptosis H Zhang et al of breast cancer cells, indicating the presence of PDCD4-mediated apoptotic pathway in other cell types. In our present data, PDCD4-antisense expression was less effective for the recovery of cell growth inhibited by TGF-b1 than for that by Smad7 (compare Figures 6b and 8b) despite PDCD4 expression was almost depressed by the antisense construct.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We have observed that PDCD4 expression was upregulated in Hep3B but rarely in HepG2 cells by TGF-b1 treatment (unpublished data). Recently, Afonia et al (2004) have reported that PDCD4 overexpression induced apoptosis PDCD4 in TGF-b1-induced apoptosis H Zhang et al of breast cancer cells, indicating the presence of PDCD4-mediated apoptotic pathway in other cell types. In our present data, PDCD4-antisense expression was less effective for the recovery of cell growth inhibited by TGF-b1 than for that by Smad7 (compare Figures 6b and 8b) despite PDCD4 expression was almost depressed by the antisense construct.…”
Section: Discussionmentioning
confidence: 98%
“…H Zhang et al gene expression is controlled by interleukins in NK cells (Azzoni et al, 1998) and upregulated by Vitamin A in breast cancer cells (Afonia et al, 2004). In chicken cells, PDCD4 gene expression is regulated by the transcription factor, myb-1 (Schlichter et al, 2001a, b).…”
Section: Pdcd4 In Tgf-b1-induced Apoptosismentioning
confidence: 99%
“…Because ATRA and most retinoids control cell proliferation via apoptosis among several other mechanisms in a variety of cancers Toma et al, 1997;Kotake-Nara et al, 2002;Afonja et al, 2004;Simeone and Tari, 2004) and also because of the cell cycle analysis data that suggests accumulation of cell in the sub-G phase, the apoptotic potential of our RAMBAs was evaluated. Retinoic acid metabolism blocking agents-induced apoptosis in MCF-7 and T47D cells was examined in three independent experiments with ATRA and 4-HPR as positive controls.…”
Section: Apoptosis Induced By Rambasmentioning
confidence: 99%
“…Pdcd4 was initially shown to suppress tumor development in an in vitro mouse keratinocyte model of tumor promotion (Cmarik et al, 1999). More recently, decreased expression of Pdcd4 has been implicated in the development and progression of human lung, colon, liver and breast cancer (Chen et al, 2003;Afonja et al, 2004;Zhang et al, 2006;Mudduluru et al, 2007). Pdcd4 expression is controlled by multiple mechanisms.…”
Section: Introductionmentioning
confidence: 99%